Hydraulic conditioning to manage potable water discolouration. Issue 1 (9th October 2017) - Sharpe, Rebecca L.; Biggs, Catherine A.; Boxall, Joby B.
Abstract : Results are reported from studies conducted using a unique laboratory-based, full-scale, temperature-controlled pipe facility to examine the impact of conditioning shear stress on discolouration risk, as characterised by bulk water samples (turbidity, iron and manganese) and biofilm pipe wall measurements. The facility uniquely allowed for replication of the dynamics of an operational network but with rigorous control, thus yielding fully representative results overcoming the limitations of bench-scale or operational studies. The effect of the daily variation in flow (and boundary shear stress) was observed to be greater than the effect of the average daily flow rate at reducing discolouration risk. This is useful for informing operation and maintenance strategies, specifically that regularly imposing cycles of flow variation are more effective than increasing total average flow rates at limiting discolouration risk. The application of such knowledge aids the development of cost-effective, proactive, operational interventions to manage discolouration.